DISKRIMINASI HARGA BERBASIS GENDER (PINK TAX) : PELANGGARAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Yustisha, Ammi (Universitas Ekasakti, 2023)
The practice of gender-based price discrimination is known as the